Implementasi Perpres No. 125 Tahun 2016 tentang Penanganan Pengungsi dari Luar Negeri (The Implementation of Presidential Regulation Number 125 of 2016 on the Handling of International Refugees) - Novianti Novianti (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2019)
The existence of asylum seekers and international refugees is a problem in Indonesia and until now Indonesia has not ratified the 1951 Convention and the 1967 Protocol on the Status of Refugees. Although the two has not yet ratified, the Government has issued Presidential Regulation Number 125 of 2016 on the Handling of International Refugees as mandated by Article 27 of the Law on Foreign Relations. For that reason, the problem discussed in this paper is on how to regulate the handling of refugees and how to implement Presidential Regulation on the Handling of International Refugees. The result of the study indicates that the regulations related to the handling of international refugees is not in accordance with international law and the Law Number 6 of 2011 on Immigration. According to the Presidential Regulation the process of returning the refugees is either voluntary return or deportation. The choices are not in conflict with Indonesia's obligation to uphold refugee protection standards and the principle of non-refoulement. Therefore, it is necessary to harmonize the Presidential Regulation and the Law on Immigration. AbstrakKeberadaan pencari suaka dan pengungsi dari luar negeri menjadi persoalan di Indonesia. Sampai saat ini, Indonesia belum meratifikasi Konvensi 1951 dan Protokol 1967. Meskipun belum meratifikasi kedua ketentuan internasional tersebut, Pemerintah telah menerbitkan Perpres No. 125 Tahun 2016 tentang Penanganan Pengungsi dari Luar Negeri sebagai amanat dari Pasal 27 UU No. 37 Tahun 1999 tentang Hubungan Luar Negeri. Sehubungan dengan itu, permasalahan dalam tulisan ini adalah bagaimana pengaturan penanganan pengungsi luar negeri dan bagaimana implementasi Perpres No. 125 Tahun 2016. Hasil penelitian menunjukkan bahwa pengaturan terkait penanganan pengungsi dari luar negeri tidak sesuai dengan ketentuan hukum internasional dan hukum nasional yaitu UU No. 6 Tahun 2011 tentang Keimigrasian. Berdasarkan Perpres tersebut, proses pemulangan pengungsi dilakukan pilihan secara sukarela atau deportasi. Hal ini tidak bertentangan dengan kewajiban Indonesia untuk menjunjung tinggi standar pelindungan pengungsi dan prinsip non-refoulement. Oleh karena itu, perlu harmonisasi antara Perpres tersebut dan UU Keimigrasian.